Use of peers, community lay persons and Village Health Team (VHT) members improves six-week postnatal clinic (PNC) follow-up and Early Infant HIV Diagnosis (EID) in urban and rural health units in Uganda: A one-year implementation study. Issue 1 (June 2015) - Namukwaya, Zikulah; Barlow-Mosha, Linda; Mudiope, Peter; Kekitiinwa, Adeodata; Matovu, Joyce; Musingye, Ezra; Ssebaggala, Jane; Nakyanzi, Teopista; Abwooli, Jubilee; Mirembe, Dorothy; Etima, Juliane; Bitarakwate, Edward; et al.
Abstract Background Effective Prevention of Mother to child Transmission of HIV (PMTCT) relies heavily on follow-up of HIV-infected women and infants from antenatal, through postnatal, to the end of the breastfeeding period. In Uganda, postnatal (PNC) follow-up remains below 50 % creating a missed opportunity for linkage to comprehensive HIV care and early infant diagnosis (EID). We evaluated the use of HIV infected peer mothers (peers), community lay persons and Village health team (VHT) members to improve PNC follow up and EID in urban and rural health units. Methods Study participants were HIV-infected women recruited from antenatal clinics at three urban clinics (Mulago, Rubaga and Mengo hospitals) and one rural health centre (Mpigi Health centre IV) between January and September 2010. The women were followed through delivery and the mother-infant pairs for the 6-week postnatal visit and up to 14 weeks for EID. Peers, community lay persons and VHT members were identified and trained in basic PMTCT and reproductive health (RH). They were then assigned to study clinic to support and follow study participants, their partners and infants through provision of health education, counseling, home visits, and phone call reminders. Six week PNC attendance was measured as a proportion of mother-infant pairs that returned for the 6-week postnatal follow up visit (5–8 weeks) while EID was measured as the proportion of HIV-exposed live birth that had an HIV test done by 14 weeks of age. Data at baseline (one year before the intervention) was compared with that during the one year study period among study participants and HIV infected women and their HIV-exposed infants in the whole clinic population. Results A total of 558 HIV-infected pregnant women were recruited for the study, 47 mother-infant pairs were censured before 6 weeks due to stillbirth (14), infant death < 6 weeks (23), death of participant (04) and loss to follow up before delivery (6). 401/511 (78.5 %) of mother-infant pairs returned to the study clinics at six-week, while 441/511 (86.3 %) infants were tested for HIV infection by 14 weeks of age. The baseline six-week PNC follow up was 37.7 % and increased during the study period to 78.5 % and 39.1 % among study participants and whole clinic population respectively, an incremental difference of 39.4 % (P  < 0.001). EID increased from a baseline of 53.6 % to 86.3 % and 65.8 % among study and whole clinic population respectively during the study period, an incremental difference of 20.5 % (P  < 0.001). Conclusions Use of peers, community lay persons and VHT members led to a significant increase in six-week postnatal follow up of HIV infected women and EID among HIV exposed infants in the four study clinics. Our study supports the use of peers to improve early postnatal follow up and EID and should be implemented in other health units to support the PMTCT cascade.